People’s Financial Choice Depends on their Previous Task Success or Failure - Sekścińska, Katarzyna (Frontiers in Psychology, 2015)
Existing knowledge about the impact of the experience prior to financial choices has been limited almost exclusively to single risky choices. Moreover, the results obtained in these studies have not been entirely consistent. For example, some studies suggested that the experience of success makes people more willing to take a risk, while other studies led to the opposite conclusions. The results of the two experimental studies presented in this paper provide evidence for the hypothesis that the experience of success or failure influences people’s financial choices, but the effect of the success or failure depends on the type of task (financial and non-financial) preceding a financial decision. The experience of success in financial tasks increased participants’ tendency to invest and make risky investment choices, while it also made them less prone to save. On the other hand, the experience of failure heightened the amount of money that participants decided to save, and lowered their tendency to invest and make risky investment choices. However, the effects of the experience of success or failure in non-financial tasks were exactly the opposite. The presented studies indicated the role of the specific circumstances in which the individual gains the experience as a possible way to explain the discrepancies in the results of studies on the relationship between the experience prior to financial choice with a tendency to take risks.